2020
DOI: 10.1371/journal.pone.0231900
|View full text |Cite
|
Sign up to set email alerts
|

Functional, anatomical and diffusion tensor MRI study of radiology expertise

Abstract: Background Repeated practice to acquire expertise could result in the structural and functional changes in relevant brain circuits as a result of long-term potentiation, neurogenesis, glial genesis, and remodeling. Purpose The goal of this study is to use task fMRI to study the brain of expert radiologists performing a diagnosis task where a series of medical images were presented during fMRI acquisition for 12s and participants were asked to choose a diagnosis. Structural and diffusion-tensor MRI were also ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“… Reilhac et al (2013) reported deactivation in the right superior parietal lobules, which was closely related to visual attention in radiologists. Ouellette et al (2020) also found deactivation in the left SPL in radiologists, which was attributed to more efficient control of visual attention supported by accelerated eye-tracking data. We propose that decreased ALFF in SPL also reflects a similar trend.…”
Section: Discussionmentioning
confidence: 63%
“… Reilhac et al (2013) reported deactivation in the right superior parietal lobules, which was closely related to visual attention in radiologists. Ouellette et al (2020) also found deactivation in the left SPL in radiologists, which was attributed to more efficient control of visual attention supported by accelerated eye-tracking data. We propose that decreased ALFF in SPL also reflects a similar trend.…”
Section: Discussionmentioning
confidence: 63%
“…Kesler et al ( 2011 ) found significantly increased activation of the SFG in visual tasks, which participated in online monitoring and manipulation of task-related information. Ouellette et al found lower activation of the lateral SFG in trained radiologists while they viewed medical images, suggesting that WM is a crucial component of radiology expertise and more efficient in radiologists (Ouellette et al, 2020 ). In our current study, different trends in the bilateral SFG showed that the increased DC values in the left SFG and decreased DC values in the right SFG were closely associated with WM when utilizing radiological expertise.…”
Section: Discussionmentioning
confidence: 99%
“…This perceptual specialty is acquired through intensive training during which hundreds of cases are reviewed [ 3 , 6 ]. Recently, a few studies investigated the functional anatomy of visual expertise under tasks using the expertise model of radiologists [ 10 12 , 18 ]. Haller et al [ 11 ] and Ouellette et al [ 18 ] observed activation in the ventral visual pathway, including the right fusiform gyrus (FG), and higher-order brain regions, such as the left inferior frontal gyrus in radiologists in differentiating X-ray films than novices.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a few studies investigated the functional anatomy of visual expertise under tasks using the expertise model of radiologists [ 10 12 , 18 ]. Haller et al [ 11 ] and Ouellette et al [ 18 ] observed activation in the ventral visual pathway, including the right fusiform gyrus (FG), and higher-order brain regions, such as the left inferior frontal gyrus in radiologists in differentiating X-ray films than novices. Harley et al specifically investigated the visual pathway and reported engagement of FG when radiologists detected abnormalities in chest radiographs [ 10 ].…”
Section: Introductionmentioning
confidence: 99%